Monitoring the state anti-crisis management of economic security of the Ukraine banking institutions - Iryna Mihus; Yana Koval; Serhiy Laptev; Olha Bala; Marta Kopytko (Verslas: Teorija ir praktika / Business: Theory and Practice, 2020)
The study and synthesis of research showed that the most often anti-crisis management is considered, firstly, as a complex of preventive measures that is comprehensive and aimed at preventing and eliminating unfavorable phenomenon for business using existing resources and survival potential, and secondly, as implementation of special procedures for the withdrawal of economic agents from the crisis, in particular such as sanitation, restructuring, bankruptcy, liquidation. The main element of system control at the macro level is the state regulation of the economy, one of the most important tasks of which is the elimination of failures of functioning of the market mechanism at the micro level, that is, the creation of conditions for overcoming the crisis phenomenon in the activities of business entities. This task is solved by developing and implementing measures of state anti-crisis regulation. The main purpose of the article is to carry out diagnostics and monitoring in the system of state crisis management of economic security of banking institutions of Ukraine. In addition, the purpose of the article is also to study and systematize the technology of state anti-crisis regulation of banking institutions of Ukraine. The article highlights the criteria for assessing the system of anti-crisis management of financial stability of banking institutions at macro and micro levels. The diagnostics in the anti-crisis regulation of banking institutions of Ukraine is carried out. The main components of the monitoring in the system of state anti-crisis management in the banking institutions of Ukraine are noted. The levers of state anti-crisis regulation in the banking institutions of Ukraine are described. The measures and technologies of state anti-crisis management at the level of banking institutions of Ukraine are proposed. The results of the study can be used by banking institutions of Ukraine, the National Bank of Ukraine, financial institutions, etc.
Keywords: G01; G21; G28; H12; H56; 650; monitoring; mechanisms of public administration; economic security; anti-crisis management; banking institutions